Simulation and techno-economic analysis of production processes of novel generation L-Asparaginases using recombinant Escherichia coli and Pichia pastoris. - Ferreira, Adamo Eduardo da Silva (2022)
L-Asparaginase (L-asparagine amino hydrolase, E.C.3.5.1.1) is an important enzyme that presents antitumor properties being clinically used in the treatment of Acute Lymphoblastic Leukemia. The distinct microbial formulations available on the market differ in pharmacokinetics, technology, dosage, treatment protocol, and market value. Despite being a biopharmaceutical widely used as a first or second line of treatment, its production is restricted to a few laboratories around the world. Besides, techno-economic analyzes of the L-Asparaginase production process are scarce in the literature. The main objective of this work is to carry out a complete techno-economic analysis of the production of novel L-Asparaginases featuring two distinct technologies: PEGylation and glycosylation, produced by recombinant Escherichia coli and Pichia pastoris, respectively. Through laboratory studies described in the literature, the scale-up and simulation of different scenarios were carried out using SuperPro Designer software aiming at the production of 1 kg of enzyme/year. For the production of PEG-Asparaginase by Escherichia coli, the best scenario presented a unit production cost of 7.57 USD/mg, and the following economic indexes: Return on Investment of 26.8%; Internal Rate of Return of 19.9%; Net Present Value of 16.06 million USD; and Payback Time of 3.7 years. Regarding the production of glycosylated Crisantaspase by Pichia pastoris, the unit cost of production was estimated at 3.42 USD/mg, with the following economic indexes: Return on Investment of 44.2%; Internal Rate of Return of 33.5%; Net Present Value of 34.75 million USD; and Payback Time of 2.3 years. Currently, the values of the possible alternatives for the treatment of Acute Lymphoid Leukemia available on the market, which feature similar technology, vary between 15.66 USD/mg (Spectrila) and 36.70 USD/mg (Oncaspar). The attractive economic parameters corroborate with the potential for the development of improved and competitive biopharmaceuticals, capable not only of supplying the annual Brazilian demand but also of driving technological and industrial development.